Customer Loyalty: Security, Sales Promotion, And E-Service Quality - Sherly Eka Saputri; Lorena Dara Putri Karsono (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This research aims to analyze the effect of security, sales promotion, and e-service quality on customer loyalty of OVO e-wallet users in Kudus City. This research uses a type of field research or a quantitative approach. The research population is OVO e-wallet users in Kudus City, whose total is not known with certainty. The sampling technique used in this study used accidental sampling with 100 respondents of OVO e-wallet users in Kudus City. The data collection technique used is a questionnaire, and the analysis technique is multiple linear regressions with the help of the SPSS version 26 program. The results showed that security positively and significantly affects customer loyalty. Sales promotion positively and significantly affects customer loyalty. E-service quality positively and significantly affects customer loyalty. Security, sales promotion, and e-service quality significantly simultaneously affect customer loyalty. Companies can use this research as a source of information used to improve security, sales promotion, and e-service quality so that OVO e-wallet customer loyalty can also increase.